Design and Implementation of “AugMedicine: Lung Cases,” an Augmented Reality Application for the Medical Curriculum on the Presentation of Dyspnea - Pieterse, Arianne D.; Hierck, Beerend P.; de Jong, Peter G. M.; Kroese, Jelger; Willems, Luuk N. A.; Reinders, Marlies E. J. (Frontiers in Virtual Reality, 2020)
Introduction: Augmented Reality is a technique that enriches the real-life environment with 3D visuals and audio. It offers possibilities to expose medical students to a variety of clinical cases. It provides unique opportunities for active and collaborative learning in an authentic but safe environment. We developed an Augmented Reality application on the clinical presentation of shortness of breath (dyspnea), grounded on a theoretical instructional design model. Methods: A team of various stakeholders (including medical teachers and students) was formed to design the application and corresponding small group learning session, grounded on principles of instruction as described by Merrill. Evaluation was performed by an explorative questionnaire, consisting of open and closed questions (Likert scales), covering user experience, content and physical discomfort. Results: Multiple interactive cases of dyspnea were designed. The application plays back audio samples of abnormal lung sounds corresponding to a specific clinical case of dyspnea and displays a 3D model of the related pulmonary pathologies. It was implemented in the medical curriculum as an obligatory small group learning session scheduled preceding clinical clerkships. Prior knowledge was activated prior to the learning session. New knowledge was acquired with the application by solving an authentic problem based on a real patient case. In total 110 students participated in the study and 104 completed the questionnaire. 85% of the students indicated that the virtually auscultated lung sounds felt natural. 90% reported that the augmented reality experience helped them to better understand the clinical case. The majority of the students (74%) indicated that the experience improved their insight in the portrayed illness. 94.2% reported limited or no physical discomfort. Discussion: An Augmented Reality application on the presentation of dyspnea was successfully designed and implemented in the medical curriculum. Students confirm the value of the application in terms of content and usability. The extension of this Augmented Reality application for education of other healthcare professionals in currently under consideration.